Crime and the imaginary of disaster: post-apocalyptic fictions and the crisis of social order - Yar, Majid (Palgrave Pivot, 2015)
This study explores the 'imaginary of disaster' that appears in popular fictions about the apocalyptic breakdown of society. Focusing on representations of crime, law, violence, vengeance and justice, it argues that an exploration post-apocalyptic story-telling offer us valuable insights into social anxieties.--Provided by publisher